Intersectional Approach to People Displaced by Environmental Causes - Bueso Izquierdo, Patricia (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2022)
Forced displacement caused by environmental causes are increasing in recent years. Many of those who migrate for these reasons are expelled from their land by climate change effects which entails political partner in turn cause armed conflicts. This creates a growing number of migrants group can lead the next “crisis of refugees”. In this situation, it will provide vital assistance and protection. It is then necessary to ask, which theoretical framework could assess the application of the current international legislation and the European migration policies to protect persons displaced by environmental causes? The intersectional approach in relation with the dynamic links made by UNHCR should generate new responses that future progress towards human mobility regulations in the XXI Century.